Fair Perception as a Condition for Polygamy Permit Application at Mojokerto Religious Court - Masadah, Masadah; Muhammad, Afif (International Journal of Law Dynamics Review, 2023)
This article aims to describe the application for polygamy at the Mojokerto Religious Court, the administrative complexities and the process for allowing husbands to practiceoligamy. The judge can give consideration in granting permission for polygamy proposed by the husband. The research method used is a qualitative research method with a descriptive-analytical approach, this research uses judge interview data and then qualitative analysis is carried out with deductive methods. The results showed that hakim at the Mojokerto Religious Court interpreted fair in polygamy as proportional, that is, having to adjust and place something according to its place. The husband in terms of providing for his wives bypaying attention to the needs of each wife. The factor or reason for the granting orrejection of the application for polygamy permission at the Religious Court is that the judge gets confidence that the husband will be able to act fairly with the judge's suspicion that is faced with evidence before the court. The evidence in the trial process includes letter evidence, statements of the applicant and respondent, witness statements that will assess from the evidence the ability and readiness of the husband to polygamy.